OCT assessment of non-cavitated occlusal carious lesions by variation of incidence angle of probe light and refractive index matching. (July 2017) - Park, Kyung-Jin; Haak, Rainer; Ziebolz, Dirk; Krause, Felix; Schneider, Hartmut
Abstract: Objectives: This study evaluated (1) the detection and assessment of non-cavitated occlusal carious lesions by spectral domain optical coherence tomography (SD-OCT) and (2) the impact of varying angle of incidence (AI) of probe light and refractive index matching (RIM). Methods: Nine extracted human molars with 18 occlusal lesions (ICDAS code 2) were visually selected. 18 regions of interest (ROI) were imaged with SD-OCT under varying AI (0°, ±5°, ±10°, ±15°) and with/without application of glycerine at 0°. X-ray micro computed tomography (μCT) was used as a validation standard. μCT and OCT signals were categorized according to the lesion extent: 1-sound, 2-lesion limited to half of enamel, 3-lesion limited to enamel, 4-lesion into dentin. Agreement between both methods was assessed. Intra- and inter-examiner reproducibility analyses were conducted. Statistics: Cohen's kappa coefficient (κ), Spearman's rho correlation ( rs ) and Wilcoxon test (α = 0.05). Results: Slight to moderate agreement (κ = 0.153) between μCT and OCT was obtained at an AI of 0° (Wilcoxon: p = 0.02). With variation of Al a substantial agreement (κ = 0.607) was observed (p = 0.74). Spearman's correlation between both methods was 0.428 at 0°, 0.75 with varying AI and 0.573 with glycerine. Kappa values for intra-and inter-examiner analysis ranged between 0.81 and 0.88 and between 0.25 and 0.73, respectively. Conclusion: Variation of AI improves the detectability of non-cavitated occlusal carious lesions. RIM can enhance signal-to-noise ratio. Clinical relevance: OCT could provide additional diagnostic information in single and longitudinal assessments of occlusal carious lesions.